Host susceptibility to MERS-CoV infection, a retrospective cohort study of the 2015 Korean MERS outbreak - Ko, Jae-Hoon (J Infect Chemother, 2018)
To evaluate host susceptibility factors to Middle East respiratory syndrome coronavirus (MERS-CoV) infection, we conducted a retrospective cohort study from the single largest exposure event of the 2015 Korean MERS outbreak. A total of 175 patients were closely exposed to a super-spreader, 26 of which were infected (14.9%). In a multivariate analysis, history of autologous stem cell transplantation (HR, 31.151; 95% CI, 5.447–178.145; P < 0.001) and tachypnea at ED (HR, 4.392; 95% CI, 1.402–13.761; P = 0.011) were significantly associated with MERS-CoV infection.